BUILDING STUDENT TEACHERINTERACTION PATTERN IN EFL-CLT CLASSROOM - Mad Riyanto (DIDAKTIKA, 2016)
One of the priorities of language teachers is to ensure classes are interesting andengaging. Learners’ different backgrounds and individual preferences, however,make each class unique. The objective of EFL classroom adopting Communicative language teaching (CLT) approach is to be fluent and communicative competence in genuine communication (Hatch1978; Nunan, 1987). In this context, EFL teachers play a pivotal role in creating a comfortable environment to persuade the students in communicative interaction. By a good communication between the teacher and students the teaching learning process will be more effective. The teachers can motivate and encourage students to communicate with them well, if interaction has been done. Teachers as the source of second language or foreign language should give meaningful interactions to the students. Krashen(1981,1985)states to facilitate such meaningful interactions, EFL teachers serve as a source of L2 input to the students.The writer attempts to build the pattern of student teacher interaction and reveals the factors inhibit teachers to interact with students.